Risky Business : Political Instability and Greenfield Foreign Direct Investment in the Arab World - Burger, Martijn; Ianchovichina, Elena; Rijkers, Bob (World Bank, Washington, DC, 2014)
Which foreign direct investments are most affected by political instability? Analysis of quarterly greenfield investment flows into countries in the Middle East and North Africa from 2003 to 2012 shows that adverse political shocks are associated with significantly reduced investment inflows in the non-resource tradable sectors. By contrast, investments in natural resource sectors and non-tradable activities appear insensitive to such shocks. Consistent with these patterns, the significant reduction in investment inflows in Arab Spring affected economies was starkest in the non-resource manufacturing sector. Political instability is thus associated with increased reliance on non-tradables and aggravated resource dependence. Conversely, how intensified political instability affects aggregate foreign direct investment is critically contingent on the initial sector composition of these flows.